Effect of remittance-sending countries' type on financial development in recipient countries: can the pandemic make a difference? - Forhad, Md. Abdur Rahman; Alam, Gazi Mahabubul; Rahman, Md. Toabur (Multidisciplinary Digital Publishing Institute, 2023)
This study examines the effect of remittances on selected recipient countries’ financial development. Using weights for bilateral remittances from 1990 to 2015, this study calculates the weighted gross national income per capita of remittance-sending countries. This study then uses the weighted gross national income as an instrument to address the endogeneity between remittance and financial development. Using the instrument variable (IV) model, this study finds that remittances from low-skilled migrant-abundant sending countries have different effects than the highly skilled labor-abundant sending countries. Assuming the Gulf Cooperation Council (GCC) countries as a source of low-skilled and the Group of Seven (G7) as the source of high-skilled labor-abundant sending countries, remittance from relatively low-skilled emigrants has a greater impact on financial inclusion in the recipient countries than their high-skilled counterparts. In contrast, remittance from high-skilled countries has a greater impact on the development of the stock market. Similar types of effects of remittance on financial development have also been observed during the COVID-19 pandemic. The results suggest that policymakers should provide better foreign employment opportunities and improved transaction and investment policies in the home financial markets.